2016
DOI: 10.1186/s12889-016-3418-x
|View full text |Cite
|
Sign up to set email alerts
|

Equality in sexual health promotion: a systematic review of effective interventions for black and minority ethnic men who have sex with men

Abstract: BackgroundOver the past decade, new diagnoses of HIV have increased eightfold among men who have sex with men (MSM) of other or of mixed ethnicity in the UK. Yet there is little intervention research on HIV among black and minority ethnic (BME) MSM. This article aimed to identify effective HIV and sexual health prevention strategies for BME MSM.MethodsWe searched three databases PubMed, Scopus and PsychInfo using a combination of search terms: MSM or men who have sex with men and women (MSMW); Black and Minori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 46 publications
(98 reference statements)
0
24
0
Order By: Relevance
“…Despite the sexual health inequalities faced by BME MSM and high HIV incidence in this population, there has been limited empirical research into the possible HIV risk factors in this population. 22 Accordingly, the present study explores the relationships between HIV knowledge and reported sexual health and sexual behaviour in a sample of BME MSM in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the sexual health inequalities faced by BME MSM and high HIV incidence in this population, there has been limited empirical research into the possible HIV risk factors in this population. 22 Accordingly, the present study explores the relationships between HIV knowledge and reported sexual health and sexual behaviour in a sample of BME MSM in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Most HIV and sexual health promotion interventions focus primarily on components of sexual health knowledge and behavior (e.g., condom use, PrEP awareness and uptake, HIV testing, etc. ), with less acknowledgment of social psychological constructs, such as identity, authenticity, and social connectedness (Fish et al, 2016). This is important for increasing the acceptability of sexual health promotion in the sauna.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, effective interventions should be informed by social psychological research that captures the views, perceptions, and behaviors of the target population in the target context, that is, the diverse identities of the people whom we wish to target (Fish, Papaloukas, Jaspal, & Williamson, 2016). This demonstrates the need for a social psychological approach to sexual health promotion, focusing on identity.…”
Section: Hiv Risk and Prevention In The Gay Saunamentioning
confidence: 99%
“…As universities become increasingly diverse, there is a need for them to be cognizant of growing diversity in both pedagogy and pastoral support (Jaspal, 2015). A culturally competent approach to sexual health education is necessary given that this will increase the likelihood of engagement with, and acceptability of, a sexual health education program among students from diverse backgrounds (Fish, Papaloukas, Jaspal, & Williamson, 2016).…”
Section: Toward a University Sexual Health Education Programmentioning
confidence: 99%